MULTILATERAL INSTRUMENTS IN INTERNATIONAL TAX LAW: LEGAL MECHANISMS FOR ADAPTING BILATERAL TAX TREATIES TO THE DIGITAL AGE (World Conference on Social Sciences, Law and Public Policy, 2026)
This paper examines the paradigm shift in international tax law from a strictly bilateral framework to an integrated multilateral architecture, driven by the rapid digitalization of the global economy. For nearly a century, the allocation of taxing rights relied on physical presence, primarily through the Permanent Establishment (PE) standard. However, the rise of borderless digital business models and the proliferation of unilateral Digital Services Taxes (DSTs) have rendered this traditional framework structurally obsolete, necessitating unprecedented, coordinated global reform. This research evaluates the legal mechanics, functional architecture, and comparative efficacy of key multilateral instruments designed to surgically adapt the existing network of over 3,500 bilateral double taxation treaties without requiring full renegotiation. It analyzes the pioneering 2017 BEPS Multilateral Instrument (MLI) and its complex compatibility clauses, the OECD’s Pillar One Multilateral Convention (MLC) aimed at establishing a legal fiction of digital nexus, and the Pillar Two Subject to Tax Rule (STTR) MLI designed to protect the tax bases of developing nations. Furthermore, it contrasts these highly rigid, OECD-led initiatives with the United Nations’ Fast-Track Instrument (FTI), which offers a modular, pro-developing nation alternative. Ultimately, the analysis highlights the systemic tensions,interpretative challenges, and severe geopolitical hurdles — particularly concerning United States domestic ratification — that currently threaten the global viability of these innovative multilateral legal mechanisms.